2015
DOI: 10.1016/j.chembiol.2015.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated Lipid Assimilation by Mycobacteria Requires Auxiliary cis-trans Enoyl CoA Isomerase

Abstract: Mycobacterium tuberculosis (Mtb) can survive in hypoxic necrotic tissue by assimilating energy from host-derived fatty acids. While the expanded repertoire of β-oxidation auxiliary enzymes is considered crucial for Mtb adaptability, delineating their functional relevance has been challenging. Here, we show that the Mtb fatty acid degradation (FadAB) complex cannot selectively break down cis fatty acyl substrates. We demonstrate that the stereoselective binding of fatty acyl substrates in the Mtb FadB pocket is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…The correlative research shows that enoyl-CoA hydratase (ECH) catalyzes the second step in the physiological β-oxidation pathway of fatty acid metabolism [67,68]. It is worth noting that the energy provided from fatty acids to organisms could be blocked without this enzyme, and the absence of this protein would lead to an increase in levels of unsaturated fatty acids, especially oleic acid and linoleic acid [69]. Aldehyde dehydrogenase (ALDH) is used as a reliable marker to separate stem cells and has been stated to play an important role in cell proliferation and protection [70,71].…”
Section: Most Enzymes In C Oleifera Are Key Proteins Involved In Fatmentioning
confidence: 99%
“…The correlative research shows that enoyl-CoA hydratase (ECH) catalyzes the second step in the physiological β-oxidation pathway of fatty acid metabolism [67,68]. It is worth noting that the energy provided from fatty acids to organisms could be blocked without this enzyme, and the absence of this protein would lead to an increase in levels of unsaturated fatty acids, especially oleic acid and linoleic acid [69]. Aldehyde dehydrogenase (ALDH) is used as a reliable marker to separate stem cells and has been stated to play an important role in cell proliferation and protection [70,71].…”
Section: Most Enzymes In C Oleifera Are Key Proteins Involved In Fatmentioning
confidence: 99%
“…It has been previously shown that fadD6 function as a fatty acid transporter, and its protein level was higher in Mtb H37Rv bacilli in a dormant state than in Mtb in the exponential growth phase [41]. The family of Ech proteins of Mtb is involved in the degradation of cis fatty acids [42]. EchA2 is a monofunctional enoyl CoA isomerase [41] may be involved in unsaturated fatty acid metabolism and essential for Mtb survival in lipid-rich environments [10].…”
Section: Main Transcriptomic Changes Between Ut127 and Ut205mentioning
confidence: 99%
“…Altogether, these results indicate that SCOfadAB gene products can display catalytic activities attributable to E. coli FadBA complex when expressed in the E. coli Δ fadBA mutant, namely: enoyl-CoA hydratase, 3-hydroxyacyl-CoA dehydrogenase, and 3-ketoacyl-CoA thiolase (Yang et al, 1988 ; Srivastava et al, 2015 ). Furthermore, the complementation studies also suggest that the other β-oxidation enzymes (FadL, FadD, and FadE) present in E. coli can functionally interact with SCOfadAB gene products for exogenous FA assimilation.…”
Section: Resultsmentioning
confidence: 92%
“…Neighbor-joining phylogenetic trees based on amino acid sequence of FadB enzymes from different organisms, group SCO6732 and SCO6789 together with FadB from the actinomycetes Mycobacterium tuberculosis (64 and 63% identity, respectively; Srivastava et al, 2015 ) and Rhodococcus equi (64 and 61% identity, respectively; Kelly et al, 2002 ; Figure 1C ). In contrast, SCO6026 is placed near to FadB sequences from Gram (−) bacteria: E .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation